Anti-aging and anti-plasticizing blended microporous polymer membrane as well as preparation method and application thereof

By preparing a composite mixed -pore polymer membrane with a polymer polymer containing Tellercoline and a carboxyl -containing polypelide, the interconnection of the hydrogen bond solves Facing the problem of plasticization and aging, it has achieved efficient gas separation performance and stable membrane performance.

CN119345925APending Publication Date: 2025-01-24TIANJIN UNIV OF SCI & TECH
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411483865.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The self-porous microporous polymer film containing Tellene faces aging problems caused by plasticization and pore structure collapse during the purification process of natural gas.

Method used

A blended microporous polymer membrane is prepared by using a film-forming process of a self-polymerizing microporous polymer containing Teleg base and a carboxyl-containing polyimide, utilizing the carboxyl groups in the polyimide and the self-polymerizing microporous The Teleger base structure of the polymer forms hydrogen bonds that anchor each other, reducing the risk of plasticization and improving anti-aging properties.

Benefits of technology

It has reduced the plasticization problem of membrane materials during the natural gas purification process, significantly improved the anti-aging performance of the membrane, and ensured the stability of gas separation performance, especially under high-pressure conditions, which is better than traditional membrane materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119345925A_ABST
    Figure CN119345925A_ABST
Patent Text Reader

Abstract

The invention provides an anti-aging and anti-plasticizing blended microporous polymer membrane as well as a preparation method and application thereof, and relates to the field of membrane materials. The preparation method of the blended microporous polymer membrane comprises the following steps: preparing an auto-polymerization microporous polymer containing Teler's alkali and polyimide containing carboxyl; and preparing the anti-aging and anti-plasticizing blended microporous polymer gas separation membrane from the self-polymerized microporous polymer containing the Teler's alkali and the polyimide containing carboxyl by adopting a membrane forming process. Characteristic functional groups (carboxyl groups connected with polyimide) in the blended components and the intrinsic structure (Teller's base) of the self-polymerized microporous polymer generate hydrogen bond interaction, so that molecular chains of the two polymers are mutually anchored, and the problem of membrane material plasticization caused by high-pressure CO2 and CH4 in natural gas is solved; and by limiting the rotation of the molecular chain, the anti-aging performance of the membrane material is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of membrane materials, and in particular to an anti-aging and anti-plasticization blended microporous polymer membrane and a preparation method and application thereof. Background Art

[0002] Natural gas is clean, efficient, green and environmentally friendly. It is an important part of my country's energy and one of the important options for achieving carbon peak. my country's Bohai Oilfield currently has nearly 180 oil and gas production platforms (including land terminals, etc.), with an annual output of about 30 million tons. Most of the oil fields have low gas-to-oil ratios, and the annual associated gas is about 1.67 billion m3. 3 In addition to being used as fuel gas or reinjected, a large part of the associated gas is vented or burned due to the lack of a pipeline system or insufficient pipeline capacity, resulting in huge energy waste and environmental pollution, and leading to a variety of problems such as pipeline transportation and reduced calorific value.

[0003] Membrane separation has the advantages of being green, efficient and easy to operate in the process of natural gas purification because it does not undergo phase change and does not require adsorbents. Gas separation membrane materials, as core components, directly determine the separation purity and efficiency of gases. Microporous polymers, as an emerging material, have shown higher gas permeability and suitable selectivity than traditional commercial membrane materials (polycarbonate, polyamide, cellulose acetate, polysulfone and polyimide, etc.) in the field of gas separation, and are expected to become the core raw materials of the new generation of gas separation membranes. For example, the carbon dioxide permeability of the spirocyclic PIM-1 is as high as 10,000 Barrer, and its selectivity for CO2 / N2 and CO2 / CH4 is 10 and 18 respectively; the selectivity of the triptycene TPIMs for CO2 / CH4 and H2 / CH4 is as high as 31 and 53 respectively; and the highly microporous polymers of the triptycene type, PIM-Trip-TB and PIM-EA-TB, synthesized by Professor McKeown's research group, have a specific surface area of ​​up to 1028 m 2 / g (much higher than the specific surface area of ​​PIM-1 720 m 2 / g), and the comprehensive performance of H2 / CH4, H2 / N2, and O2 / N2 far exceeds the Robeson upper limit in 2008. However, due to the structural characteristics of the self-polymerized microporous polymer containing tegumentum, it not only faces the plasticization problem faced by traditional polymers in the natural gas purification process, but also faces the aging problem caused by the collapse of its own pore structure. Summary of the invention

[0004] Therefore, the technical problem to be solved by the present invention is to overcome the plasticization problem faced by the self-polymerized microporous polymer membrane containing tolerine in the prior art during the natural gas purification process and the aging problem caused by the collapse of its own pore structure, thereby providing an anti-aging and anti-plasticization blended microporous polymer membrane and its preparation method and application.

[0005] To achieve the above object, the present invention provides the following technical solutions: In a first aspect, the present invention provides a method for preparing an anti-aging and anti-plasticization blended microporous polymer membrane, comprising the following steps: (1) preparing a self-polymerizing microporous polymer containing tegument base and a polyimide containing a carboxyl group; (2) A self-polymerizing microporous polymer containing tegumentum and a carboxyl-containing polyimide are prepared by a membrane-forming process to obtain an anti-aging and anti-plasticization blended microporous polymer gas separation membrane.

[0006] Furthermore, in step (1), the molar ratio of the self-polymerizing microporous polymer containing Teregulin and the carboxyl-containing polyimide is 1-100:1-100, preferably 2-10:1, and more preferably 10:1, 5:1 or 2:1.

[0007] Furthermore, at least one of the self-polymerizing microporous polymer containing tolerogen and the polyimide containing carboxyl group has a specific surface area greater than 300 m 2 / g, preferably, at least one of the self-polymerized microporous polymer containing Teregulin and the carboxyl-containing polyimide has a specific surface area greater than 800 m 2 / g.

[0008] Furthermore, the structural formula of the self-polymerized microporous polymer containing tegumentine is as shown in formula (I):

[0009] (I) In formula (I), N is an integer of 10 to 1000, preferably an integer of 10 to 120, more preferably an integer of 100 to 120, and most preferably 100. A is selected from the following structural formula: , , , .

[0010] Furthermore, the structural formula of the carboxyl-containing polyimide is shown in formula (II):

[0011] (II) In formula (II), wherein X is an integer of 1 to 200, preferably an integer of 20 to 40, more preferably an integer of 20 to 30, and most preferably 20, Y is an integer of 1 to 200, preferably an integer of 20 to 120, more preferably an integer of 100 to 120, and most preferably 100, A is selected from the following structural formula: , , , , , , ; B is selected from the following structural formula: , , , , , ; C is selected from the following structural formula: , , , , , , , .

[0012] Furthermore, the preparation method of the carboxyl-containing polyimide comprises the following steps: 4,4'-(hexafluoroisopropylidene) diphthalic anhydride (6FDA), 9,9-bis(4-aminophenyl)fluorene (FDA), and 3,5-diaminobenzoic acid (3,5-DMBA) are dissolved in m-cresol, and isoquinoline is added as a catalyst. The reaction is heated. After the reaction is completed, the solution is poured into dichloromethane to dissolve, and the obtained solution is poured into ethanol for precipitation. The obtained initial product is repeatedly filtered, washed, and dried to remove the solvent to obtain a 6FDA-FDA-3,5-DMBA polymer, wherein: The molar ratio of 4,4'-(hexafluoroisopropylidene)diphthalic anhydride, 9,9-bis(4-aminophenyl)fluorene, and 3,5-diaminobenzoic acid is 2-10:1-5:1-5, preferably 6:5:1; The molar volume ratio of 3,5-diaminobenzoic acid to m-cresol is 1-1.5:1-10 mol / mL, preferably 1:10 mol / mL; The molar ratio of 3,5-diaminobenzoic acid to isoquinoline is 1-5:0.1-0.5, preferably 1:0.2; Heating reaction conditions: 160 ℃ for 4-6 h; The volume ratio of m-cresol, dichloromethane and ethanol is 1-10:5-50:50-500, preferably 1:5:50.

[0013] Furthermore, in step (2), the membrane forming process is selected from: preparing a homogeneous membrane by a solvent evaporation method, preparing a heterogeneous flat membrane by a non-solvent phase conversion method, and preparing a hollow fiber membrane by a hollow spinning technology.

[0014] Furthermore, the method for preparing a homogeneous membrane by solvent evaporation method comprises: dissolving a self-polymerizing microporous polymer containing tegument base and a carboxyl-containing polyimide in an organic solvent to obtain a mixed solution; pouring the mixed solution into a container, and after the solvent evaporates, pouring an appropriate amount of methanol into it for immersion, and drying to obtain a homogeneous membrane, wherein: The mass volume ratio of the self-polymerized microporous polymer containing tegument base to the organic solvent is 0.1-0.2:10-20 g / mL; the mass volume ratio of the polyimide containing carboxyl group to the organic solvent is 0.06-0.07:10-20 g / mL; The organic solvent is selected from at least one of dichloromethane (DCM), N-methylpyrrolidone (NMP), N,N-dimethylacetamide (DMF), dimethyl sulfoxide (DMSO), and tetrahydrofuran (THF); The methanol immersion time is 2~3 h; the drying temperature is 80~100℃, and the time is 2~3 h.

[0015] Furthermore, the mass volume ratio of the self-polymerized microporous polymer containing tegumentine to the organic solvent is 0.1-0.2:10 g / mL; the mass volume ratio of the carboxyl-containing polyimide to the organic solvent is 0.06-0.07:10 g / mL; The methanol immersion time is 2 h; the drying temperature is 80 °C and the time is 2 h.

[0016] In a second aspect, the present invention provides an anti-aging and anti-plasticization blended microporous polymer membrane obtained by the preparation method.

[0017] In a third aspect, the present invention provides the use of the anti-aging and anti-plasticization blended microporous polymer membrane obtained by the preparation method in gas separation.

[0018] Furthermore, the anti-aging and anti-plasticization blended microporous polymer membrane is used for natural gas purification or carbon capture.

[0019] The technical solution of the present invention has the following advantages: 1. The present invention prepares a blended microporous polymer membrane by using a membrane-forming process to mix a self-polymerizing microporous polymer containing tegument base and a carboxyl-containing polyimide. The membrane utilizes the characteristic functional groups in the blended components (carboxyl groups connected to the polyimide) and the intrinsic structure of the self-polymerizing microporous polymer (tegument base) to produce hydrogen bond interactions, so that the two polymer molecular chains are anchored to each other, thereby reducing the plasticization problem of the membrane material caused by high-pressure CO2 and CH4 in natural gas. In addition, by limiting the rotation of the molecular chains, the anti-aging performance of the membrane material is improved.

[0020] 2. The blended microporous polymer membrane provided by the present invention has CO2 / CH4 selectivity, especially the CO2 / CH4 gas separation performance of the I6FFD-1 blended microporous polymer membrane prepared in Example 1 exceeds the Robeson upper limit in 2008, so it has certain application prospects in natural gas purification.

[0021] 3. The blended microporous polymer membrane provided by the present invention has CO2 / N2 selectivity and high CO2 permeability, and therefore has certain application prospects in carbon capture. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0023] Figure 1 It is a graph of the anti-aging performance of the film samples prepared in Example 1, Comparative Example 1 and Comparative Example 3 of the present invention; Figure 2 It is the infrared spectra of the film samples prepared in Examples 1 to 3 and Comparative Examples 1 to 2 of the present invention; Figure 3 It is the X-ray photoelectron spectrum of the film samples prepared in Examples 1 to 3, Comparative Example 1 and Comparative Example 3 of the present invention. DETAILED DESCRIPTION

[0024] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.

[0025] The self-polymerized microporous polymer ITTB containing Teregulin used in the embodiment of the present invention was synthesized with reference to the method reported by Zhang Caili et al., and the steps are as follows: 47 mmol 4,4′-diamino-3,3′-dimethylbiphenyl (DAT) and 236 mmol diethoxymethane (DMM) were respectively added to a three-necked round-bottom flask with a magnet at 0°C; 1.1 mol trifluoroacetic acid (TFA) was dripped into the reaction mixture, and after the addition of trifluoroacetic acid, the reaction mixture was heated to 20°C and stirred for 94 h, and the mixture was injected into NH3·H2O solution to obtain a solid product, which was then filtered and purified three times in chloroform and methanol; and the TB polymer (ITTB) was dried in a vacuum oven at 80°C overnight, with a specific surface area of ​​911.83 m² / g. The preparation method refers to the following literature: "Zhang C, Fu L, Tian Z, et al. Post-crosslinking of triptycene-based Tröger's base polymers with enhanced natural gas separation performance [J] . Journal of Membrane Science, 2018, 556: 277-284".

[0026] The synthetic route of ITTB is as follows:

[0027] Where m=100.

[0028] In the examples, each abbreviation represents the following raw materials: 6FDA: 4,4'-(hexafluoroisopropylidene)diphthalic anhydride; FDA: 9,9-bis(4-aminophenyl)fluorene; 3,5-DMBA: 3,5-diaminobenzoic acid.

[0029] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the art can be used. The raw materials or instruments used are all conventional products that can be obtained commercially, including but not limited to the raw materials or instruments used in the examples of this application.

[0030] Example 1 This embodiment provides a method for preparing a blended microporous polymer membrane, and the specific steps are as follows: (1) Synthesis of carboxyl-containing polyimide PI: 6 mol 6FDA, 5 mol FDA, and 1 mol 3,5-DMBA were dissolved in 10 mL m-cresol, 0.2 mol isoquinoline was added as a catalyst, and the mixture was heated to 160 °C and reacted at this temperature for 6 h. After the reaction was completed, the solution was poured into 50 mL dichloromethane to dissolve, and the resulting solution was poured into 500 mL ethanol to precipitate. The resulting initial product was repeatedly filtered, washed, and dried to remove the solvent to obtain a 6FDA-FDA-3,5-DMBA polymer with a specific surface area of ​​830.01 m² / g, recorded as PI-CO; The structural formula of 6FDA-FDA-3,5-DMBA polymer is shown below:

[0031] Where X=20, Y=100.

[0032] (2) Preparation of blended microporous polymer membrane: Weigh 0.018 g of PI-CO and 0.182 g of ITTB (molar ratio 1:10) and dissolve them in 10 mL of chloroform. Stir for 3 h until the polymer is completely dissolved. Pour the resulting mixed solution into a glass culture dish. After the solvent evaporates, pour in an appropriate amount of methanol and soak for 2 h. Dry at 80 °C for 2 h to obtain the I6FFD-1 mixed matrix membrane.

[0033] Example 2 This embodiment provides a method for preparing a blended microporous polymer membrane, and the specific steps are as follows: (1) Synthesis of carboxyl-containing polyimide PI: 6 mol 6FDA, 5 mol FDA, and 1 mol 3,5-DMBA were dissolved in 10 mL m-cresol, 0.2 mol isoquinoline was added as a catalyst, and the mixture was heated to 160 °C and reacted at this temperature for 6 h. After the reaction was completed, the solution was poured into 50 mL dichloromethane to dissolve, and the resulting solution was poured into 500 mL ethanol to precipitate. The resulting initial product was repeatedly filtered, washed, and dried to remove the solvent to obtain a 6FDA-FDA-3,5-DMBA polymer, which was recorded as PI-CO. (2) Preparation of blended microporous polymer membrane: Weigh 0.033 g of PI-CO and 0.1667 g of ITTB (molar ratio 1:5) and dissolve them in 10 mL of chloroform. Stir for 3 h until the polymer is completely dissolved. Pour the resulting mixed solution into a glass culture dish. After the solvent evaporates, pour in an appropriate amount of methanol and soak for 2 h. Dry at 80 °C for 2 h to obtain an I6FFD-2 mixed matrix membrane.

[0034] Example 3 This embodiment provides a method for preparing a blended microporous polymer membrane, and the specific steps are as follows: (1) Synthesis of carboxyl-containing polyimide PI: 6 mol 6FDA, 5 mol FDA, and 1 mol 3,5-DMBA were dissolved in 10 mL m-cresol, 0.2 mol isoquinoline was added as a catalyst, and the mixture was heated to 160 °C and reacted at this temperature for 6 h. After the reaction was completed, the solution was poured into 50 mL dichloromethane to dissolve, and the resulting solution was poured into 500 mL ethanol to precipitate. The resulting initial product was repeatedly filtered, washed, and dried to remove the solvent to obtain a 6FDA-FDA-3,5-DMBA polymer, which was recorded as PI-CO. (2) Preparation of blended microporous polymer membrane: Weigh 0.067 g of PI-CO and 0.133 g of ITTB (molar ratio 1:2) and dissolve them in 10 mL of chloroform. Stir for 3 h until the polymer is completely dissolved. Pour the resulting mixed solution into a glass culture dish. After the solvent evaporates, pour in an appropriate amount of methanol and soak for 2 h. Dry at 80 °C for 2 h to obtain an I6FFD-3 mixed matrix membrane.

[0035] Comparative Example 1 This comparative example provides a method for preparing a self-polymerized microporous polymer membrane (TB), and the specific steps are as follows: Weigh 0.2 g of ITTB and dissolve it in 10 mL of chloroform. Stir for 3 h until the polymer is completely dissolved. Pour the resulting mixed solution into a glass petri dish. After the solvent evaporates, pour in an appropriate amount of methanol and soak for 2 h. Dry at 80 °C for 2 h to obtain a TB self-polymerized microporous polymer membrane.

[0036] Comparative Example 2 This comparative example provides a method for preparing a self-polymerized microporous polymer membrane (PI-CO), and the specific steps are as follows: 0.2 g of PI-CO (prepared according to Example 1) was weighed and dissolved in 10 mL of chloroform, and stirred for 3 h until the polymer was completely dissolved. The resulting mixed solution was poured into a glass culture dish, and after the solvent evaporated, an appropriate amount of methanol was poured in and soaked for 2 h. The mixture was dried at 80°C for 2 h to obtain a PI-CO self-polymerized microporous polymer membrane.

[0037] Comparative Example 3 This comparative example provides a method for preparing a blended microporous polymer membrane, and the specific steps are as follows: (1) Synthesis of PI: Add 0.3484 g (1 mmol) FDA to a three-necked flask, add 10 mL of m-cresol, start mechanical stirring, add 0.4442 g (1 mmol) 6FDA after the diamine is completely dissolved, add one to two drops of isoquinoline (catalyst), heat to 120 °C and keep for 6 hours until the solution has a certain viscosity, then stop heating. After cooling to room temperature, pour the polymer into methanol and filter it three times, and dry it in a vacuum oven at 80 °C overnight to obtain white powder PI. Its synthesis route is as follows:

[0038] Where n=100.

[0039] (2) Synthesis of PI / TB: Weigh 0.0182 g PI and 0.1818 g ITTB (molar ratio 1:5), add 10 mL chloroform and stir until completely dissolved, then pour into a 60 mm glass culture dish. Wait for the solvent to completely evaporate and condense into a film at room temperature. After the film is completely dry, soak it in methanol. After standing overnight, clamp the film between a clean glass plate and dry it in a vacuum oven at 80 °C for 2 h to obtain a PI / TB mixed matrix membrane.

[0040] Experimental Example 1 This experimental example aims to test the gas permeation flux (H2, N2, O2, CH4, CO2) and selectivity (H2 / N2, H2 / CH4, O2 / N2) of the blended microporous polymer membrane prepared in Example 1 and some high-performance polymer membranes reported in the prior art. The gas separation performance of the membrane material was tested by the constant volume variable pressure method, referring to the method described in the reference "Journal of Membrane Science, Simultaneously enhanced gas separation and anti-aging performance of intrinsic microporous polyimide by dibromo substitution, 2023, 687, 122081." The results are shown in Table 1.

[0041] Table 1 Gas separation performance of I6FFD-1 blended microporous polymer membrane and some high performance polymer membranes

[0042] The CTTB and MTTB in the above membrane samples were synthesized by the method described in the reference "Macromolecules, Enhanced GasSeparation Properties of Tröger's Base Polymer Membranes Derived from PureTriptycene Diamine Regioisomers, 2020 53 (5), 1573-1584."; the PIM-1 was synthesized by the method described in the reference "Macromolecule, Physical Aging, Plasticization and Their Effects onGas Permeation in "Rigid" Polymers of Intrinsic Microporosity, 2015, 48 (18), 6553-6561."; the TPIM-1 was synthesized by the method described in the reference "Advanced Materials, Energy-efficient hydrogen separation by AB-type ladder-polymer molecular sieves, 2014, 26 (39), 6696-6700.". PI / TB was prepared with reference to Comparative Example 3.

[0043] As shown in Table 1, by comparison, it can be found that the I6FFD-1 blend membrane prepared in Example 1 has excellent H2 / N2, H2 / CH4, and O2 / N2 selectivity, and also has good permeation flux. Although the selectivity is slightly lower than that of PI / TB, the permeation flux is much greater than that of PI / TB, which is also in line with the Trade-off effect of polymer membranes. Compared with PI / TB blend membrane samples, I6FFD-1 has the best comprehensive performance.

[0044] Experimental Example 2 This experimental example aims to detect the gas permeation flux (N2, O2, CH4, CO2) and selectivity (CO2 / CH4, O2 / N2) of the blended microporous polymer membranes prepared in Examples 1 to 3 and the self-polymerized microporous polymer membranes prepared in Comparative Examples 1 to 2, and the detection method is the same as that of Experimental Example 1. The results are shown in Table 2.

[0045] Table 2 Gas separation performance of TB membrane, PI-CO membrane and I6FFD blend membranes with different ratios

[0046] As shown in Table 2, compared with the original TB membrane, the permeability coefficients of the I6FFD blend membranes prepared by adding different proportions of PI-CO are reduced to varying degrees, and the permeability coefficient decreases with the increase of the proportion of PI-CO in the I6FFD membrane. For the O2 / N2 gas pair, the O2 permeability coefficient of the original TB membrane is 993 Barrer, while the permeability coefficient of the I6FFD-1 blend membrane after adding the PI-CO component is reduced to 785 Barrer, and the permeability coefficient of N2 is also reduced from the original 180 Barrer to 132 Barrer. For the CO2 / CH4 gas pair, after adding different proportions of PI-CO, the CO2 permeability coefficient of the blend membrane is reduced from the original 3446 Barrer to 3242 Barrer, and the permeability coefficient of CH4 is reduced from the original 218 Barrer to 169 Barrer. This is due to the low permeability coefficient of the PI-CO component introduced into the blend membrane. The separation performance of the original TB membrane for O2 / N2 gas pair is 5.5, and the separation performance of the I6FFD-1 blend membrane with a small amount of PI-CO component introduced is increased to 5.9, which is higher than the original TB membrane and PI-CO membrane. This shows that the introduction of a small amount of PI-CO component can improve the selectivity of the I6FFD-1 blend membrane. This may be because the -COOH of the polymer PI-CO produces a hydrogen bond interaction with the N in the polymer TB unit, which affects the arrangement and thermal motion of the polymer molecular chain, thereby increasing the selectivity of the gas separation membrane.

[0047] Experimental Example 3 This experimental example aims to study the anti-plasticization performance of the blended microporous polymer membrane prepared in Example 2, and is specifically characterized by measuring the gas permeation flux (H2, N2, O2, CH4, CO2) of the membrane sample as it changes with gas pressure. Determination method: Cut the membrane into a suitable size, measure its thickness, and then package and fix it with aluminum foil tape and AB glue to ensure that it is intact and leak-proof. Then put the sample into the membrane pool, seal it with aluminum foil tape and rubber, open the downstream valve, vacuum degas for 24 hours, and then place the membrane at 1, 2, 3, 4, and 20 atm for permeation testing. The detection method is the same as that of Experimental Example 1. The results are shown in Table 3.

[0048] Table 3 Anti-plasticization properties of I6FFD-2 blended microporous polymer membranes

[0049] Table 3 shows the plasticization performance test results of the I6FFD-2 blend membrane placed in the pressure range of 1~20 atm. It can be seen that when the feed pressure increases from 1 atm to 20 atm, the permeation flux of H2 increases from 2890.02 Barrer to 3899.33 Barrer, the permeation flux of N2 increases from 156.78 Barrer to 208.18 Barrer, the permeation flux of O2 increases from 672.56 Barrer to 932.64 Barrer, the permeation flux of CH4 increases from 169.38 Barrer to 221.11 Barrer, and the permeation flux of CO2 increases from 2921.19 Barrer to 3921.09 Barrer. It can be seen that the permeation fluxes of these gases increase to varying degrees with the increase of feed pressure, and the selectivity of CO2 / CH4 and O2 / N2 does not change significantly. When the pressure is higher than the critical plasticization pressure, gases such as CO2 can expand the glassy polymer and loosen the polymer matrix. When plasticization occurs, the permeability increases with the increase of pressure and the selectivity decreases. Therefore, the anti-plasticization ability of the polymer film should be increased. The anti-plasticization ability of the blended film in this experiment is due to the formation of the blended structure of carboxyl-containing PI-CO and TB, which limits the mobility of the chain and inhibits its plasticization in CO2 / CH4 and O2 / N2.

[0050] Experimental Example 4 The purpose of this experimental example is to study the anti-aging performance of the blended microporous polymer membrane prepared in Example 1. At the same time, the membrane samples prepared in Comparative Examples 1 and 2 are used as controls. The gas permeability of the membrane samples is measured over time. The detection method is the same as that in Experimental Example 1. The original TB membrane, I6FFD-1 blended membrane and PI / TB blended membrane are exposed to room temperature (20°C, 1atm) for up to 90 days of monitoring, and the gas permeability tests are performed on the membranes after aging for 0, 30, and 90 days, respectively.

[0051] The results are shown in Table 4 and Figure 1 shown.

[0052] Table 4 Comparison of aging properties of TB film, I6FFD-1 blend film and PI / TB blend film

[0053] As shown in Table 4 and Figure 1As shown in the figure, after 30 days of physical aging, the permeability of the original TB membrane has dropped significantly, especially for large molecular gases, such as N2, which dropped from the initial 180 Barrer to 67 Barrer, a decrease of 76%. The I6FFD-1 blended membrane also dropped after 30 days, such as the N2 permeability dropped from the initial 132 Barrer to 83 Barrer, a decrease of only 37%. The PI / TB blended membrane had the smallest drop, which may be due to the low gas separation performance of the polymer PI itself, which greatly reduced the permeability of the gas separation membrane after blending with TB. It is worth mentioning that after 30 days of aging, the O2 and N2 permeability of the I6FFD-1 blend membrane is 521 Barrer and 83 Barrer, while the O2 and N2 permeability of the original TB membrane is 438 Barrer and 67 Barrer; the CO2 and CH4 permeability of the I6FFD-1 blend membrane is 2001 Barrer and 96 Barrer, while the CO2 and CH4 permeability of the original TB membrane is 1640 Barrer and 87 Barrer. At this time, the gas separation performance of the CO2 / CH4 gas pair of the original TB is lower than the Robeson upper limit, while the I6FFD-1 blend membrane is still higher than the Robeson upper limit.

[0054] Experimental Example 5 This experimental example aims to study the infrared spectra of the blended microporous polymer membranes prepared in Examples 1 to 3. The infrared spectra were obtained by a NICOLET 6700 Fourier transform infrared spectrometer produced by FEI, USA.

[0055] The infrared spectra of the original TB film and the I6FFD blend films with different ratios are shown in Figure 2. Figure 2 As shown in the figure, it can be observed that the carbonyl stretching band of the I6FFD blend membrane has changed compared with the TB membrane, and as the proportion of PI-CO in the I6FFD blend membrane continues to increase, the carbonyl stretching band also moves to a higher wave number (from 1714 cm -1 To 1720 cm -1 ), which is due to the -COOH group on the main chain of the PI-CO polymer and the OH…N hydrogen bond interaction between the N on the main chain of the TB polymer. −1 The typical characteristics of hydrogen bonding can be observed at about 3300 cm −1The broad characteristic peaks appearing at are caused by the stretching vibration of the -OH group in PI-CO, while the -OH characteristic peaks in I6FFD-2 and I6FFD-3 are significantly weakened compared to the -OH characteristic peaks in I6FFD-1. This is because the proportion of PI-CO in the I6FFD-2 blend film continues to increase, and more PI-CO provides more -COOH groups, which produce more OH...N hydrogen bond interactions with N on the main chain of the TB polymer. The infrared spectrum results confirmed that hydrogen bond interactions changed the characteristic peaks of the functional groups.

[0056] Experimental Example 6 This experimental example aims to study the X-ray photoelectron spectra of the blended microporous polymer membranes prepared in Examples 1 to 3. The X-ray photoelectron spectra were obtained using an XRD-6100 diffractometer produced by Shimadzu Corporation of Japan.

[0057] The X-ray photoelectron spectra of the original TB, PI / TB and I6FFD with different ratios are shown in Figure 2. Figure 3 As shown. In the I6FFD blend films with different ratios, the core signal of the N1s peak becomes broader, and the peak intensity at 399.08 eV is slightly higher than that of the PI / TB blend film. This is due to the N⋯OH hydrogen bond interaction between the -COOH group contained in PI-CO and the N on TB. It can be observed in the figure that compared with the PI / TB blend film, the I6FFD blend films with different ratios have a new energy peak at 400.88 eV, which is also due to the hydrogen bond interaction between the -COOH group in PI-CO and the N on TB. The above observations show that the hydrogen bond interaction between the N atom and the -COOH group will cause the shift of the N1s core signal, which also shows that hydrogen bond interactions can induce XPS shifts.

[0058] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.

Claims

1. A method for preparing an anti-aging and anti-plasticization blended microporous polymer membrane, characterized in that: The following steps are involved: (1) preparing a self-polymerizing microporous polymer containing tegument base and a polyimide containing a carboxyl group; (2) A self-polymerizing microporous polymer containing tegumentum and a carboxyl-containing polyimide are prepared by a membrane-forming process to obtain an anti-aging and anti-plasticization blended microporous polymer gas separation membrane.

2. The method for preparing the anti-aging and anti-plasticization blended microporous polymer membrane according to claim 1, characterized in that: In step (1), the molar ratio of the self-polymerized microporous polymer containing Teregulin and the carboxyl-containing polyimide is 1-100:1-100, preferably 2-10:1, more preferably 10:1, 5:1 or 2:1; at least one of the self-polymerized microporous polymer containing Teregulin and the carboxyl-containing polyimide has a specific surface area greater than 300 m 2 / g.

3. The method for preparing the anti-aging and anti-plasticization blended microporous polymer membrane according to claim 1, characterized in that: The structural formula of the self-polymerized microporous polymer containing tegumentine is shown in formula (I): (I) In formula (I), N is an integer of 10 to 1000, preferably an integer of 10 to 120, more preferably 100, A is selected from the following structural formula: 、 、 、 ; The structural formula of the carboxyl-containing polyimide is shown in formula (II): (II) In formula (II), X is an integer of 1 to 200, preferably an integer of 20 to 40, more preferably 20, Y is an integer of 1 to 200, preferably an integer of 20 to 120, more preferably 100, A is selected from the following structural formula: 、 、 、 、 、 、 ; B is selected from the following structural formula: 、 、 、 、 、 ; C is selected from the following structural formula: 、 、 、 、 、 、 、 。 4. The method for preparing the anti-aging and anti-plasticization blended microporous polymer membrane according to claim 1, characterized in that: The preparation method of the carboxyl-containing polyimide comprises the following steps: 4,4'-(hexafluoroisopropylidene)diphthalic anhydride, 9,9-bis(4-aminophenyl)fluorene, and 3,5-diaminobenzoic acid are dissolved in m-cresol, and isoquinoline is added as a catalyst, and the reaction is heated. After the reaction is completed, the solution is poured into dichloromethane to dissolve, and the obtained solution is poured into ethanol for precipitation. The obtained primary product is repeatedly filtered, washed, and dried to remove the solvent to obtain a 6FDA-FDA-3,5-DMBA polymer, wherein: The molar ratio of 4,4'-(hexafluoroisopropylidene)diphthalic anhydride, 9,9-bis(4-aminophenyl)fluorene, and 3,5-diaminobenzoic acid is 2-10:1-5:1-5, preferably 6:5:1; The molar volume ratio of 3,5-diaminobenzoic acid to m-cresol is 1-1.5:1-10 mol / mL, preferably 1:10 mol / mL; The molar ratio of 3,5-diaminobenzoic acid to isoquinoline is 1-5:0.1-0.5, preferably 1:0.2; Heating reaction conditions: 160 ℃ for 4-6 h; The volume ratio of m-cresol, dichloromethane and ethanol is 1-10:5-50:50-500, preferably 1:5:

50.

5. The method for preparing the anti-aging and anti-plasticization blended microporous polymer membrane according to claim 1, characterized in that: In step (2), the membrane forming process is selected from: preparing a homogeneous membrane by a solvent volatilization method, preparing a heterogeneous flat membrane by a non-solvent phase conversion method, and preparing a hollow fiber membrane by a hollow spinning technology.

6. The method for preparing the anti-aging and anti-plasticization blended microporous polymer membrane according to claim 5, characterized in that: The method for preparing a homogeneous membrane by solvent evaporation method comprises: dissolving a self-polymerizing microporous polymer containing tegument base and a carboxyl-containing polyimide in an organic solvent to obtain a mixed solution; pouring the mixed solution into a container, and after the solvent evaporates, pouring an appropriate amount of methanol into the container for immersion, and drying to obtain a homogeneous membrane, wherein: The mass volume ratio of the self-polymerized microporous polymer containing tegument base to the organic solvent is 0.1-0.2:10-20 g / mL; the mass volume ratio of the polyimide containing carboxyl group to the organic solvent is 0.06-0.07:10-20 g / mL; The organic solvent is selected from at least one of dichloromethane, N-methylpyrrolidone, N,N-dimethylacetamide, dimethyl sulfoxide, and tetrahydrofuran; The methanol immersion time is 2~3 h; the drying temperature is 80~100 ℃ and the time is 2~3 h.

7. The method for preparing the anti-aging and anti-plasticization blended microporous polymer membrane according to claim 6, characterized in that: The mass volume ratio of the self-polymerized microporous polymer containing tegument base to the organic solvent is 0.1-0.2:10 g / mL; the mass volume ratio of the polyimide containing carboxyl group to the organic solvent is 0.06-0.07:10 g / mL; The methanol immersion time is 2 h; the drying temperature is 80 °C and the time is 2 h.

8. The anti-aging and anti-plasticization blended microporous polymer film obtained by the preparation method according to any one of claims 1 to 7.

9. Application of the anti-aging and anti-plasticization blended microporous polymer membrane obtained by the preparation method according to any one of claims 1 to 7 in gas separation.

10. The use according to claim 9, characterized in that: The anti-aging and anti-plasticization blended microporous polymer membrane is used for natural gas purification or carbon capture.

Citation Information

Cited By

  • Polyimide composite material, polyimide gas separation membrane, preparation method and application

    CN121226726A

  • A polyimide composite material, a polyimide gas separation membrane, and a preparation method and application thereof

    CN121226726B